Motivation for Virtual Purchase of Higgs Domino Game Players Among Bengkulu City Millenials - Monica Anggraini; Sapta Sari; Anis Endang (Jurnal ISO: Jurnal Ilmu Sosial, Politik dan Humaniora, 2022)
This study aims to determine the virtual purchase motivation of Higgs Domino game players among millennials in Bengkulu City. The researcher also used the concept of Hedonism Motivation Theory according to Gultekin and Ozer (in Utami, 2017) which has 6 elements, namely Adventure Shopping, Gratification or relaxation shopping, Value Shopping, Social Shopping, Idea shopping and Role shopping. The data were collected through interviews, observations, and literature studies. The informants in this study amounted to six millennials in Bengkulu City. The results of this study indicate that there is a hedonistic motivation that encourages millennials to make virtual purchases on the Higgs Domino game. Adventure Shopping in this study is the informant will feel an adventure that can arouse enthusiasm when buying chips. Gratification or relaxation shopping in this study is informants can forget their problems and fatigue. Value Shopping in this study is informants are more interested in buying if the seller offers a discounted price. Social Shopping in this study is informants feel happy when buying chips and interacting with the seller. The idea of shopping in this study is that the informants play games because they follow the trend. Role shopping in this research is the informant sends the chip if his friend also sends the chip for him.